Determinants of Islamic and Conventional Banking Insolvency Risk in Indonesia - Fitriyatustany Fitriyatustany; Mohammad Iqbal Irfany; Tita Nursyamsiah (Falah: Jurnal Ekonomi Syariah, 2024)
The insolvency risk has an important part in the development and sustainability of the banking industry. The fall in financial parameters due to the Covid-19 outbreak suggests that banks are at risk of insolvency. The study aims to detect and assess developments in insolvency risk in Islamic and conventional banking between 2018 and 2023. The methods used were Z-score, X-score, G-score, and panel data regression. The results indicate that internal factors, namely Loans to Assets at the Top Four Conventional Commercial Banks (BUK), Cost Income Ratio at BUK, Income Diversity, and Total Assets at Islamic Commercial Banks (BUS), have a significant negative effect on the Z-score value. External factors, namely Gross Domestic Product at BUS and BUK, have a substantial negative effect, and Interest Rates at BUK have a significant positive effect on the Z-score value. Islamic and conventional banking must preserve the bank's health by increasing capital, retaining factors important to the Z-score, and conducting additional research with more diversified variables and objects to improve efficiency and stability. A more thorough theoretical model for recognizing and controlling insolvency risk in both kinds of banking can be created using these insights. The article’s conclusions can help Indonesian banks create more effective risk management plans.